Acid-base behavior of an oligomer of 3-amino-1,2,4-triazole - Lamanna, Melisa Elsa (2011)
We report the acid-base behavior of OATA, an oligomer synthesized from 3-amino-1,2,4-triazole (ATA). We analyze the UV-vis spectroscopy at different media, and we analyze and discuss the acid-base equilibria taking into account tautomeric equilibria at different pH. The low aqueous solubility at neutral pH can be attributed to the neutral form. Indeed, OATA was synthesized in an ordinary filter paper, which can be used as a sensor for ammonia as well as endpoint indication. Using the OATA-containing paper, ammonia concentrations in a solution as low as 5 ppm could be measured.